Pengembangan Sumber Daya Manusia Pendidikan Berbasis Penilaian Kinerja - Faridah; Neni Hendaryati; Rony Yulianto (Cakrawala: Jurnal Pendidikan, 2021)
Human resource development can be done through educational programs. Performance management is based on agreement on objectives, knowledge requirements, skills, competencies, work plans and development. Performance management has the competence to be a tool for achieving cultural and behavioral change and is a way to empower employees by giving them greater control over their work and their own personal development. Educational HR consists of education staff, teaching staff, and management staff whose main task is to plan, coordinate, evaluate and follow up on the implementation and management of educational activity programs. HR development is one of the stages of strategic management, including: (1) increasing HR skills; and (2) providing capable managers for the future. Development includes activities directed at improving and growing the attitudes, skills, and knowledge of personnel.